PENGARUH PIJAT OKSITOSIN TERHADAP PRODUKSI AIR SUSU IBU DI RSUD Dr. M. HAULUSSY DAN RS TINGKAT II Prof. J.A. LATUMETEN AMBON - Ismiyanti Achmad (Poltekkes Kemenkes Maluku, 2021)
The problem of early breastfeeding has a negative impact on the baby’s life. The decrease in breast milk production in the first day after giving birth can be caused by a lack of stimulation of the hormones prolactin and oxytocin which play a very important role in the smooth production of breast milk. Efforts to stimulate the hormones prolactin and oxytocin in the mother after giving birth other than expressing breast milk can be done by doing breast care or massage. The purpose of this study was to determine the effect of oxytocin massage on breast milk production in Dr. M. Haulussy Hospital and Prof. J. A. Latumeten Hospital Level II Ambon. This research is expected to increase understanding and community participation in providing oxytocin massage to postpartum mothers and become input for other hospitals in providing oxytocin massage. The type of research used is a quasi experimental design. The sample was the first day postpartum women who were treated at Dr. M. Haulussy Hospital Ambon and Level II Hospital Prof. J.A. Latumeten Ambon on 29 September – 30 November 2018. Processing and analysis using the Mann Whitney test. The results showed that the production of breast milk in postpartum mothers after being given oxytocin massage intervention all (100%) had good breast milk production and the results of statistical tests using the Wilcoxon test obtained a P-value = 0.000 (p-value <0.05), meaning that there was an effect of oxytocin massage. on the milk production of postpartum mothers.